(untitled) (Research, Society and Development, 2023)
The temporomandibular joint (TMJ) is the most complex joint in the human body and the most used, moving around two thousand times a day on average, composed of the mandibular condyle that articulates with the squamous portion of the temporal bone (Glenoid). together with the articular meniscus, its posterior portion presents retrodiscal tissue. Its innervation and vascularization are composed respectively of the mandibular nerves, temporal atrium, posterior temporal and masseteric nerves and arteries; superficial temporal, middle meningeal and internal maxilla. Temporomandibular dysfunction is an abnormality of this joint and/or the muscles that work with the TMJ. The administration of hyaluronic acid provides unique cell renewal in addition to facilitating the nutrition of the avascular areas of the disc and articular cartilage with anti-inflammatory and analgesic properties. To obtain the necessary data, a bibliographical search was carried out in the PUBMED databases with the MeSH descriptors: “Temporomandibular Joint Dysfunction Syndrome” and "Hyaluronic acid", combined using the Boolean operator "AND" and SCIELO with the keyword "Temporomandibular Joint". Only original articles were included, in Portuguese, English and Spanish, between 1991 and 2018. In total, 482 studies were found, but only 34 were selected using the inclusion criteria. Our objective is to confirm that hyaluronic acid plays a fundamental role in the treatment of disorders, in which multidisciplinary cohesion is extremely important to contribute not only to an early diagnosis and specific management, but also to an improvement in individualized treatment, providing a greater quality of life for patients.